Continuous CO2 capture and methanation over Ni–Ca/Al2O3 dual functional materials. Issue 4 (12th January 2023) - Li, Lingcong; Wu, Ziyang; Miyazaki, Shinta; Toyao, Takashi; Maeno, Zen; Shimizu, Ken-ichi
Abstract : Continuous CO2 capture and reduction with H2 for the synthesis of CH4 was investigated using a double reactor system over Al2 O3 -supported Ni–Ca dual functional materials in the presence of O2 . Abstract : Although Ni–Ca-based dual functional materials (DFMs) have been examined for CO2 capture and reduction with H2 (CCR) for the synthesis of CH4, their performance has generally been investigated using single reactors in an oxygen-free environment. In addition, continuous CCR operations have scarcely been investigated. In this study, continuous CCR for the production of CH4 was investigated using a double reactor system over Al2 O3 -supported Ni–Ca DFMs in the presence of O2 . We found that a high Ca loading (Ni(10)–Ca(30)/Al2 O3, 10 wt% Ni, and 30 wt% CaO) was necessary for reaction efficiency under isothermal conditions at 450 °C. The optimized DFM exhibited an excellent performance (46% CO2 conversion, 45% CH4 yield, and 97% CH4 selectivity, respectively) and good stability over 24 h. The structure and CCR activity of Ni(10)–Ca(30)/Al2 O3 were studied using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectrometry (EDS), temperature-programmed desorption (TPD), and temperature-programmed surface reaction (TPSR) techniques.